The Determinant Factors of Foreign Direct Investment (FDI) on Indonesian Economy - Hanim, Wasifah; Sugiartiningsih,; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Economic capacity has a main role in developing countries, including Indonesia. Many factors can impact economic capacity in a country. This study analyses the impact of FDI on the economy using cross-section regression in 2012 and 2016. The model uses Ordinary Least Squares (OLS). Independent variables are the Human Development Index (HDI) and Labor Force in log lormal (Ln LF). Foreign Direct Investment (FDI) and Domestic Investment (DI). Dependent variable is economy capacity, measured by gross domestic regional bruto in log normal (Ln GDRB). Our results suggest that foreign direct investment had a positive impact on Indonesia’s economy in 2012 and 2016.